Development of a Brief Assessment Tool to Evaluate Early Low Nutrition Risk in Community Elderly: Creation of the Tool and Examination of Its Reliability and Criterion-related Validity - Shoji Shinkai; Miki Narita; Hiroshi Murayama; Akihiko Kitamura; Yoshinori Fujiwara (Journal of Epidemiology)
Background: To date, a simple assessment tool to evaluate early low nutrition risk in general older population has not been available. This study aimed to create such a tool and examined its reliability and criterion-related validity. Methods: 1,192 community elderly with a mean age of 74.7 (standard deviation, 5.8) years responded to a questionnaire consisting of 48 (Hatoyama) or 34 items (Kusatsu), which have been reported to be associated with nutritional state in older people. Item analysis was conducted on the 34 common items, and items were selected based on the following criteria: adequate pass rates and discriminative power, no gender and regional differences, and a certain level of commonality based on factor analysis. Next, the factor structure of the candidate items was examined through exploratory factor analysis, and confirmatory factor analysis was conducted as the final scale structure. Furthermore, Spearman’s partial rank correlation coefficients (sex- and age-adjusted) between the created index and important health indicators were examined to determine the criterion-related validity. Results: Finally, we obtained a semantic coherence of four factors (named health beliefs, dietary status, physical activity, and food-related quality of life) totaling 13 items; confirmatory factor analysis of the four-factor solution yielded good model fit values, χ2 (59) = 275.4 (P < 0.001), comparative fit index = 0.930, and root mean square error of approximation = 0.056. The factor loadings for each factor ranged from 0.43 to 0.82, indicating adequate loadings. The reliability of the index was shown to be high by Good-Poor analysis and Cronbach’s α. The index showed statistically significant correlations with all health indicators. Conclusion: We have developed a simple assessment tool to evaluate early low nutrition risk in the general older population.